Untangling the adverse effects of late-night usage of smartphone-based SNS among University students. Issue 15 (18th November 2021) - Luqman, Adeel; Masood, Ayesha; Shahzad, Fakhar; Shahbaz, Muhammad; Feng, Yang
ABSTRACT: Smartphone-based Social networking sites (SNS) use changed the ways that individuals are increasingly becoming free and flexible to engage in social media wherever and whenever they like. However, there have been few studies that ask possible adverse effects of the late-night usage of Smartphone-based SNS. The current aims to explore the effects of late-night extreme social, cognitive, and hedonic usages of social media, such as poor sleep quality (PSQ) and cognitive function depletion (CFD). Drawing from stress–strain-outcome and ego-depletion theories, we argue that late-night Smartphone-based SNS usage is a reason for sleep deprivation, thereby leading to the depletion of cognitive function with the inducement of poor academic performance. The study opted for an empirical study ( N  = 701), based on a dual theoretical model measured by using the adapted scale from well-established and reliable studies. This study determined that Smartphone-based SNS use for personal gratification at night affects PSQ, thereby relating to significant CFD during the day. Consequently, it influences the academic performance of the users. We also discussed the implications for the service provider, users, especially students, and others who are working with the dark side of SNSs use.